Targeted Genome Editing via CRISPR in the Pathogen Cryptococcus neoformans - Arras, Samantha D. M.; Chua, Sheena M. H.; Wizrah, Maha S. I.; Faint, Joshua A.; Yap, Amy S.; Fraser, James A. (PLOS ONE, 2016)
Low rates of homologous integration have hindered molecular genetic studies in Cryptococcus neoformans over the past 20 years, and new tools that facilitate genome manipulation in this important pathogen are greatly needed. To this end, we have investigated the use of a Class 2 CRISPR system in C. neoformans (formerly C. neoformans var. grubii). We first expressed a derivative of the Streptococcus pyogenes Cas9 nuclease in C. neoformans, and showed that it has no effect on growth, production of virulence factors in vitro, or virulence in a murine inhalation model. In proof of principle experiments, we tested the CAS9 construct in combination with multiple self-cleaving guide RNAs targeting the well-characterized phosphoribosylaminoamidazole carboxylase-encoding ADE2 gene. Utilizing combinations of transient and stable expression of our constructs, we revealed that functionality of our CRISPR constructs in C. neoformans is dependent upon the CAS9 construct being stably integrated into the genome, whilst transient expression of the guide RNA is sufficient to enhance rates of homologous recombination in the CAS9 genetic background. Given that the presence of the CRISPR nuclease does not influence virulence in a murine inhalation model, we have successfully demonstrated that this system is compatible with studies of C. neoformans pathogenesis and represents a powerful tool that can be exploited by researchers in the field.